Hubungan Etika Islam Dengan Ayat Al-Qur’an & As-Sunnah Dalam Pemikiran Logis - Ayu Suci Lestari; Rahdian Novan Rifky; Alihan Satra (Yayasan Al-Afif, 2026)
Abstract Islamic ethics is a fundamental aspect of Islamic teachings which regulates moral values ​​and human behavior based on the Koran and hadith. This research aims to examine the concept of Islamic ethics, the relationship between science and humanity, and the role of science in realizing human benefit. The method used is library research using various scientific sources in the form of books, journals, articles and publications obtained through Google Scholar. The research results show that Islamic ethics functions as a guide for character formation and a harmonious social life. In an Islamic perspective, science is not only oriented towards developing knowledge, but also towards increasing human dignity and the welfare of society. The concept of benefit places knowledge as a means of protecting religion, soul, reason, lineage and property. The Qur'an and hadith also emphasize the importance of thinking logically, critically and having noble morals. Thus, the integration of Islamic ethics, science, and benefit becomes an important foundation in building a life that is just, harmonious, and oriented towards spiritual values